2022
DOI: 10.3390/ani12040531
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Diet Acclimation Modify the Acute Thermal Performance of the Largest Extant Amphibian

Abstract: The Chinese giant salamander (Andrias davidianus), one of the largest extant amphibian species, has dramatically declined in the wild. As an ectotherm, it may be further threatened by climate change. Therefore, understanding the thermal physiology of this species should be the priority to formulate related conservation strategies. In this study, the plasticity in metabolic rate and thermal tolerance limits of A. davidianus larvae were studied. Specifically, the larvae were acclimated to three temperature level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We previously demonstrated cold acclimation in A. davidianus larvae, which was characterized by improved metabolic rate and locomotive performance under cold conditions [18]. In this study, we observed a comprehensive transcriptional upregulation of substrate metabolism (e.g.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…We previously demonstrated cold acclimation in A. davidianus larvae, which was characterized by improved metabolic rate and locomotive performance under cold conditions [18]. In this study, we observed a comprehensive transcriptional upregulation of substrate metabolism (e.g.…”
Section: Discussionmentioning
confidence: 58%
“…The brain, liver, tail and limb accounts for a large proportion of the individual metabolic rate and are responsible for the maintenance of locomotive activities. Their cold-induced changes can explain the increased metabolic rate and lower critical temperature in the cold-acclimated A. davidianus larvae [18]. Interestingly, we observed increased cold preference in the cold-acclimated larvae (figure 1a).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations